2017
DOI: 10.30720/ered.441775
|View full text |Cite
|
Sign up to set email alerts
|

Görme Engelli Çocuklarda Dental Braille Eğitiminin Ağız Sağlığı ve Tutumları Üzerindeki Etkileri

Abstract: Bu çalışma, görme engeli olan çocuklarda Dental Braille Eğitiminin (DBE) çocukların oral sağlık ve hijyen ile ilgili bilgi ve tutumlarına olan etkisini analiz etmeyi amaçlamaktadır. Gereç ve yöntem: Çalışmada pre-post test yönetemi kullanılmıştır. Çocuklar eğitim öncesi ve sonrası 21. günde değerlendirilmiştir. Sonuçlar: Bu çalışma, görme engelli 12 çocuğa uygulanmıştır. Elde edilen sonuçlara göre eğitim öncesi ve sonrası çocukların bilgi düzeyi (Z =-3217 ve p = 0.001, p> 0.05) ile tutumları (Z =-2724 ve p = 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 7 publications
(2 reference statements)
0
4
0
1
Order By: Relevance
“…This SLR revealed that different OHE programs/interventions were effective, either individually or combined. Indeed, almost all of the included articles with good to poor/limited quality showed significant improvements in OH status and dental disease prevention in individuals with VI 3,32–44 . Of the 21 included articles, a few with short/unspecified durations or small sample sizes concluded with only improvement in knowledge or OH among individuals with VI 20,45–48 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This SLR revealed that different OHE programs/interventions were effective, either individually or combined. Indeed, almost all of the included articles with good to poor/limited quality showed significant improvements in OH status and dental disease prevention in individuals with VI 3,32–44 . Of the 21 included articles, a few with short/unspecified durations or small sample sizes concluded with only improvement in knowledge or OH among individuals with VI 20,45–48 …”
Section: Resultsmentioning
confidence: 99%
“…It was also considered one of the best OHE interventions with significant prospects and solutions for improving OH. Braile media was used in two single-intervention studies: one pre-and post-intervention study by Taftazani et al 35 in Indonesia and one nonrandomized trial by Khurana et al 37 in India. Both studies reported that OHE using braille media significantly improved the ability of children with VI to maintain acceptable OH.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Perubahan perilaku ke arah yang lebih baik hanya dapat dilakukan melalui proses yang disengaja dengan grand design yang mencakup proses 4,13 . Metode atau cara yang digunakan untuk mengimplementasikan grand design (rencana) yang sudah disusun dapat tercapai secara optimal apabila metode yang digunakan untuk merealisasikan strategi tersebut tepat.…”
Section: Pendahuluanunclassified